Early Neonatal Antibiotic Therapy: Changes in the Microbiota and Immune System - Ikromjonova Muhlisa (KLINIK VA FUNDAMENTAL TIBBIYOT TADQIQOTLARI JURNALI, 2026)
Antibiotic therapy during the neonatal period plays an important role in the treatment and prevention of bacterial infections. However, the early use of antibiotics may negatively affect the natural formation of the intestinal microbiota. As a result, the risk of dysbiosis, immune system dysfunction, and the development of long-term metabolic and allergic diseases increases. This article analyzes the effects of early neonatal antibiotic therapy on the intestinal microbiota and the immune system.